2017
DOI: 10.1002/jmrs.212
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of aortic aneurysm and aortic dissection through 3D printing

Abstract: IntroductionThe aim of this study was to assess if the complex anatomy of aortic aneurysm and aortic dissection can be accurately reproduced from a contrast‐enhanced computed tomography (CT) scan into a three‐dimensional (3D) printed model.MethodsContrast‐enhanced cardiac CT scans from two patients were post‐processed and produced as 3D printed thoracic aorta models of aortic aneurysm and aortic dissection. The transverse diameter was measured at five anatomical landmarks for both models, compared across three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 20 publications
1
62
0
1
Order By: Relevance
“…A four-step production process was implemented to generate the patient-specific 3D liver model utilized for this study ( Figure 1) (3,6,9,10,21,24,25).…”
Section: Generation Of 3d Printed Liver Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A four-step production process was implemented to generate the patient-specific 3D liver model utilized for this study ( Figure 1) (3,6,9,10,21,24,25).…”
Section: Generation Of 3d Printed Liver Modelmentioning
confidence: 99%
“…Image visualization and processing tools within this software were used to (I) apply a median filter, reducing image noise and enhancing the anatomical boundaries for accurate segmentation; (II) segment structures of interest; and (III) export the segmented data in standard tessellation language (STL) file format as required for editing and 3D printing (10,16,18,(22)(23)(24)(25). Anatomical structures that were perceived likely to affect decisions made in surgical planning included the inferior vena cava, portal vein and associated branches, hepatic veins, hepatic artery, the tumour and associated arterial supply, and the liver body (2,3,9,23).…”
Section: Image Segmentationmentioning
confidence: 99%
“…[21][22][23][24][25] However, in a recent study, Ho et al have indicated that the variances in aortic diameter measurements between 3D printed models and 2D contrastenhanced CT images exceeded 1.0 mm, which is beyond the standard deviation of 1.0 mm. 26 This highlights the potential limitations of using anatomic landmarks to measure accuracy of 3D printed hollow models, such as heart models or aneurysmal models. By taking into account both sizes and shapes of the visceral aneurysms, the accuracy of 3D printed hollow models has been validated to further confirm the reliability of 3D printing technology.…”
mentioning
confidence: 99%
“…Further, according to a recent systematic review, majority of the current studies compared 3D printed models with original source CT or MRI data, 12,[21][22][23][24] while only a few of them compared images of the scanned 3D printed models with original source imaging data (Figure 1). 25,26 Discrepancy in measuring these dimensional diameters was shown in one of the studies with the maximal difference in vessel diameter being 3.2 mm, highlighting the limited accuracy of using diameter measurements. 26 This limitation has been addressed by using a more accurate method to determine the accuracy of 3D printed models, which is the second observation from Shibata et al study.…”
mentioning
confidence: 99%
See 1 more Smart Citation